Numerical Study of CNT Micro Fin Array for Cooling Application - Sajjad Nabizadeh; T. Fanaei Sheikholeslami; Amin Behzadmehr (Institute of Advanced Engineering and Science, 2013)
Heat removing from a microelectronic chip packaging has grand effect on performance and durability of the chip. Today’s microchips with high power densities would require efficient methods of cooling. Recently, vertical alignment CNTs, due to their superior thermal, electrical and mechanical properties, was suggested as an effective micro cooler on the level of modern electronics demands. In this paper, the cooling performance of the CNT fin structures is studied numerically. Flow of air was considered as the working fluid flow. CFD simulations have been carried out for a series of CNT micro-fin cooling architectures based on one and two dimensional fin array models. The modeling results indicate that fluid speed is the key factor in heat transfer capacity of the device. Also, the results of 2D carbon nanotube fin array model show more precise and greater thermal performance than that of 1D model. Finally, the examination of pressure drop between inlet and outlet of the cooling device is presented as an important factor which could limit the fluid speed and fin height effect on heat sink performance also investigated.